Sustainable Social Technologies In The Semiárido Of Rio Grande Do Norte – Brazil - Silva, Marcia Regina Farias da; Torres, Janine Beatriz; Dias, Nildo da Silva; Lima, Alexandre de Oliveira (Electronic Journal "Fórum Ambiental da Alta Paulista", 2021)
Along the Brazilian history, the federal government has invested in the construction of large-scale water works in the Northeastern region, aiming to fight drought in the Semiárido and to finish with the scarcity of water by means of public policies. However, the climatic context makes drought a natural characteristic of the Northeastern region and cannot be fought against, as it is a natural phenomenon in the area. The objective of the present paper is to investigate how social technologies implemented in the Semiárido have contributed to the strengthening of women’s production capacity in the Hipólito community located in the Mossoró municipality, (State of Rio Grande do Norte, Northeastern Brazil), with the implementation of fertilized cisterns, aiming at gender equality and sustainable agriculture as preconized by Agenda 2030. As a methodological procedure, a qualitative research was carried out, adopting the participatory observation and the focal group techniques. Twelve women who integrate the Mulheres em Ação group participated in the study. It was observed that women positively perceive the impacts of the social technologies of the Um Milhão de Cisternas (P1MC) and Uma Terra e Duas Águas (P1+2) programs in the Hipólito community. Moreover, agriculture practices involved in the construction of the water reuse technology in their yards yielded positive expectations regarding production by the addition of another social technology that will make a larger volume of water available to the community. It is concluded that social technologies coexisting with the Semiárido have contributed to a new territorial development model, consonant with the Semiárido characteristics.